2007
DOI: 10.1016/j.juro.2006.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid and Bone Marrow Derived Mesenchymal Stem Cells Can be Converted to Smooth Muscle Cells in the Cryo-Injured Rat Bladder and Prevent Compensatory Hypertrophy of Surviving Smooth Muscle Cells

Abstract: In this model stem cell transplantation has a limited effect on smooth muscle cell regeneration. Instead it can regulate post-injury bladder remodeling, possibly via a paracrine mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(99 citation statements)
references
References 12 publications
3
90
0
6
Order By: Relevance
“…[26][27][28][29][30] Alternatively, broad potential for differentiation and high proliferation rates make AFSC well suited for use in regenerative medicine therapies such as engineered skeletal/cardiac muscles, tendons, heart valves, and blood vessels. 11,17,[31][32][33][34][35] This study confirms our previous work on the capacity for VEGF-mediated differentiation of c-kit + AFSC into endothelial-like cells, 14 as well as illustrates the vasculogenic and perivasculogenic potential of AFSC within a threedimensional fibrin/PEG scaffold in vitro.…”
Section: Discussionsupporting
confidence: 86%
“…[26][27][28][29][30] Alternatively, broad potential for differentiation and high proliferation rates make AFSC well suited for use in regenerative medicine therapies such as engineered skeletal/cardiac muscles, tendons, heart valves, and blood vessels. 11,17,[31][32][33][34][35] This study confirms our previous work on the capacity for VEGF-mediated differentiation of c-kit + AFSC into endothelial-like cells, 14 as well as illustrates the vasculogenic and perivasculogenic potential of AFSC within a threedimensional fibrin/PEG scaffold in vitro.…”
Section: Discussionsupporting
confidence: 86%
“…Huang et al transplanted adipose-derived stem cells by intrabladder or intravenous injection resulting in improved tissue parameters and urodynamics in a rat model of overactive bladder [55]. Interestingly, De Coppi et al showed that intrabladder transplantation of amniotic fluid or bone marrow stem cells promoted post-injury bladder remodeling by a paracrine mechanism [56]. According to Hallman et al, the repair of injured renal epithelium is thought to be mediated by surviving renal proximal tubular cells that must dedifferentiate to allow for proliferation and migration necessary for epithelial regeneration.…”
Section: Bladder Dysfunction and Glomerular Injurymentioning
confidence: 99%
“…Amniotic fluid stem (AFS) cells are broadly multipotent [1] and are able to repopulate the bone marrow (BM) when transplanted into immunocompromised animals [3], while differing from pluripotent stem cells because of their inability to form teratomas [1]. AFS cells have been tested in various disease models and have been shown to contribute to lung [4], kidney [5,6], cardiac [7], and smooth muscle regeneration [8]. They can also generate myotubes in vitro [1], but very little is known about their potential to functionally engraft into regenerating skeletal muscle [9].…”
Section: Introductionmentioning
confidence: 99%